History prophylaxis against contagious diseases. Preventive measures described in Leviticus - Alfonso Fernández Vázquez (Universidad de Alicante, 2017)
Introduction: Chapters 13 and 14 of Leviticus focus on performance against leprosy, most feared throughout history that diseases like syphilis Black Death or disease. The aim of this paper is to analyze thoroughly the preventive measures of both sections from the biblical leprosy, its consequences and its impact throughout history. Method: Chapters 13 and 14 of Leviticus in three different versions of the Bible was discussed. Later, other studies and manuals communicable diseases were analyzed. Development: The findings highlight the utility of the above measures to control the of contagious diseases, quarantine appearing as the optimal solution to promote the welfare and health of the community at that time, and hygiene was considered a cornerstone in this area. Conclusions: The implementation of these interventions has produced notable benefits, especially in reducing mortality in both the Jewish population of the biblical period and subsequently other companies, highlighting some cities during the Black Death; and they have formed the pillars on which rests the current epidemiology and public health.